A política de turismo no contexto de mudanças : instituições, atores e produção de sistemas de classificação de meios de hospedagem no Brasil - Marcos Eduardo Carvalho Gonçalves Knupp (2014)
The object of study of this work is the Brazilian tourism policy with regard to the Classification of Media Hosting, one of the government's regulatory tools on the field of tourism. The latter has grown in recent decades, demonstrating its importance to the economy of many countries, becoming a new frontier of accumulation. Currently, tourism is seen by society as an important activity for human development is essential for socio-economic progress of several locations. Nevertheless, policies to guide and regulate this activity have become increasingly common, and thus a new field of interest of the State and their governments. In this sense, the Classification System Media Hosting allows the state to mediate the relationship between consumers and suppliers, correcting market arising from information asymmetry between the two faults. In Brazil, this is a creation of the state, subject to variations considering the transformations themselves by spending their modus operandi, three distinct phases can be detached from this policy. Thus, this study aims to identify the weight of the factors that have led governments to incorporate different actors in assembly Classification Media Hosting policy and resources and powers they have been granted and that its effect as to quality of the policy. As a methodological strategy adopted the exploratory, the prerogative of incipient accumulation of knowledge about the construction of tourism policies in the context of contemporary changes affecting the Brazilian State. We used a literature research and archivist through internal and external to the sector institutional documents and legal instruments and existing database to official data, in order to build historical descriptions of the Brazilian tourism policy, in parallel with the evolution of systems Classification of Media Hosting. This information was checked with interviews of key stakeholders from government agencies, private institutions and class hosting sector organizations. As a result, we demonstrated that appellants were attempts to reform the regulation of media hosting industry, however, most happened towards a partial redeployment, the forms of interaction between stakeholders have been institutionalized in the second and third time that allowed negotiation spaces between them. However, the strategy of establishments was then not adhering to classification systems, causing consumers still not prepared this official government benchmark for assessing establishments and followed setbacks denoting the intended regulatory action. We conclude that neither the reforms of State, style changes of government and changes in the macroeconomic context of tourism explain alone the different patterns identified in the classification of lodging facilities. Finally, we suggest that only by combining these propositions was possible to identify the factors changes, the prerogatives and the resources used by the different actors in the variations of this tourism policy.